HUMAN RESOURCE PRACTICES, ORGANIZATIONAL CULTURE, AND DIGITAL LEADERSHIP: DRIVERS OF EMPLOYEE PERFORMANCE IN A STATE-OWNED PLANTATION COMPANY - Thamrin; Endang Maryanti; Loly; Nasib; Affendy Abu Hassim (ZILLZELL MEDIA PRIMA, 2026)
This study analyzes the influence of compensation, engagement, competence, and organizational culture on employee performance through the application of digitalization and leadership in PTPN IV Regional I. The research is motivated by the importance of digital transformation and strengthening human resources in increasing organizational effectiveness and work productivity of state-owned plantation companies. A quantitative approach was used by collecting data through questionnaires to 264 employees using the purposive random sampling technique. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study show that compensation, engagement, competence, and organizational culture have a positive and significant effect on the implementation of digitalization, leadership, and employee performance. In addition, the implementation of digitalization and leadership has also been proven to have a positive and significant effect on employee performance. The results of mediation testing showed that the implementation of digitalization and leadership was able to mediate the relationship between compensation, engagement, competence, and organizational culture on employee performance. These findings confirm that improving employee performance requires integrating human resource management, organizational culture, digital transformation, and adaptive leadership to continuously improve work effectiveness and company competitiveness.